Farmer Group Information System at the Jombang Regency Agriculture Service - Firdaus, Thalisa; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The Jombang Regency Agriculture Service is one of the Regional Government Apparatus. The Agriculture Service has the task of assisting the Regent in government affairs and the Regional Government's authority in agriculture. In this case study, the following problems were found: the existence of agricultural extension workers whose performance was poor due to the lack of systematic monitoring. This study aimed to build an Information System for Agricultural Development Patterns in Jombang Regency. The results obtained were in the form of increased agricultural competitiveness in the era of the Industrial Revolution 4.0. With the sipotan system, the agriculture service can track, monitor, and identify regional potential by agricultural extension workers. With the sipotan system, it can be seen which extension workers are performing well and which are not.